Phylogeography of the heavily poached African common pangolin (Pholidota, Manis tricuspis ) reveals six cryptic lineages as traceable signatures of Pleistocene diversification - (:unkn) unknown (My University, 2016)
Knowledge on faunal diversification in African rainforests remains scarce. We usedphylogeography to assess (i) the role of Pleistocene climatic oscillations in the diversificationof the African common pangolin (Manis tricuspis) and (ii) the utility of ourmultilocus approach for taxonomic delineation and trade tracing of this heavily poachedspecies. We sequenced 101 individuals for two mitochondrial DNA (mtDNA),two nuclear DNA and one Y-borne gene fragments (totalizing 2602 bp). We used atime-calibrated, Bayesian inference phylogenetic framework and conducted characterbased,genetic and phylogenetic delineation of species hypotheses within African commonpangolins. We identified six geographic lineages partitioned into western Africa,Ghana, the Dahomey Gap, western central Africa, Gabon and central Africa, all divergingduring the Middle to Late Pleistocene. MtDNA (cytochrome b + control region)was the sole locus to provide diagnostic characters for each of the six lineages. TreebasedBayesian delimitation methods using single- and multilocus approaches gavehigh support for ‘species’ level recognition of the six African common pangolin lineages. Although the diversification of African common pangolins occurred duringPleistocene cyclical glaciations, causative correlation with traditional rainforest refugiaand riverine barriers in Africa was not straightforward. We conclude on the existenceof six cryptic lineages within African common pangolins, which might be of major relevancefor future conservation strategies. The high discriminative power of themtDNA markers used in this study should allow an efficient molecular tracing of theregional origin of African common pangolin seizures.
Keywords: African Research